ANALISIS MANAJEMEN RISIKO SISTEM INFORMASI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN LAMPUNG MENGGUNAKAN METODE NIST SP 800-30 - Vynda Levy Cahyani; Aristoteles Aristoteles; Alvi Yani; Tristiyanto Tristiyanto (Jurnal Pepadun, 2021)
Balai Pengkajian Teknologi Pertanian Lampung (eng. Institute for Agricultural Technology Assessment) also known as BPTP Lampung is one of the government agencies that need information systems in the management, selection, storage, and information dissemination. The application of information systems raises several risks that can disrupt activities and disadvantage in material/time for BPTP Lampung. The purpose of this research is to analyze the risk management information system of BPTP Lampung and find out the factors that affect risk occur by using NIST SP 800-30 method. The risk management information system of BPTP Lampung is implemented to anticipate the threat of risk with several stages are risk assessment, risk mitigation, and risk evaluation. There are 10 (ten) associated risks from research results, namely less communicative language, no backup of research data, no update data, multiple tasks and obligations, human error, internet access, error system, fires, natural disasters (thunderstorms, floods, earthquakes, etc.) and blackout. At a high level of risk is a less communicative language from research results by the researcher of BPTP Lampung and multiple tasks and obligations from the management of information system BPTP Lampung. The final result from the risk management of information system BPTP Lampung is a recommendation given to reduce the impact of risks that occur.